Capital regulation, heterogeneous monitoring costs, and aggregate loan quality - Kopecky, Kenneth J.; VanHoose, David (Journal of Banking & Finance, 2006)
This paper develops a banking-sector framework with heterogeneous loan monitoring costs. Banks are exposed to the moral hazard behavior of borrowers and endogenously choose whether to monitor their loans to eliminate this exposure. After analyzing an unregulated banking system, we examine several cases in which regulatory capital requirements bind the notional loan supplies of various subsets of banks. To gauge the impact of capital requirements, we define loan ‘quality’ in terms of either the ratio of monitored to total loans or the ratio of monitoring banks to total bank population. Under the assumption of a specific cross-sectional distribution of banks, our simulations show that the imposition of binding capital requirements on a previously unregulated banking system unambiguously increases the market loan rate and reduces aggregate lending, but has an ambiguous effect on loan ‘quality’. Nevertheless, once capital requirements are in place, the simulations indicate that regulators can contribute to higher overall loan ‘quality’ by toughening capital requirements.